(untitled) (Communications in Computational Physics, 2010)
An implicit high-order accurate method for solving model kinetic equations is proposed. The method is an extension of earlier work on the construction of an explicit TVD method for hybrid unstructured meshes in physical space and is illustrated on the Poiseuille flow of rarefied gas. Examples of calculations are provided for different Knudsen numbers and mesh resolutions, which illustrate the efficiency and high accuracy of the new scheme.